Self Assembly of 5,10-bis(4-hydroxyphenyl)-15,20-bis(4-pyridyl) porphyrin into Different Nanoarchitectures Using Different Methods - Gautam, Renu; Chauhan, S. M. S. (Current Organic Chemistry, 2017)
Background: Nanomaterials based on porphyrin has attracted attention for significant research due to their potential applications in diverse fields such as optoelectronic devices, catalysis, light harvesting devices, controlled-release drug delivery. The self assembly method is an effective protocol for the fabrication of nanomaterials. Objective: We synthesised an unsymmetrical porphyrin 5,10-bis(4-hydroxyphenyl)-15,20-bis(4-pyridyl) porphyrin, decorated with hydroxyl and pyridyl functional group which assist in supramolecular self assembly. Method: We used two different methods, surfactant assisted method and vaporization-condensationrecrystallization method for the self assembly of our new unsymmetrical porphyrin bearing hydrogen bonding motifs. The nanoaggregates obtained by these two different methods were well characterized by different spectroscopic techniques such as UV-visible spectra, fluorescence emission spectroscopy, scanning electron microscopy and X-ray diffraction. Results: A new unsymmetrical porphyrin was synthesized and used for the formation of different nanoaggregates. The surfactant assisted method results in fabrication of nanoboats while VCR method leads to the formation of well ordered nanospindles. Both the nanoboats and nanospindles were formed by virtue of the cooperation of the non-covalent interactions such as hydrogen bonding and ππ interactions. Conclusion: The vaporization-condensation-recrystallization method forms highly crystalline nanospindles as it induces re-crystallization based self-assemblies using externally provided thermal energy, and avoids the need for solvent molecules while surfactant assisted method requires the solvent as well external stabilizer.
Keywords: nanostructure